Changes in fish assemblage structure after implementation of Marine Protected Areas in the south western coast of Portugal - Pereira, Tadeu José (2019)
Marine Protected Areas (MPAs) are increasingly being recommended as management tools for biodiversity conservation and fisheries. With the purpose of protecting the region's biodiversity and prevent the over exploitation of marine resources, in February 2011 the no-take MPAs of Ilha do Pessegueiro and Cabo Sardão were implemented within the "Parque Natural do Sudoeste Alentejano e Costa Vicentina" (PNSACV) Marine Park, south western coast of Portugal. As such, commercial and recreational fishing became prohibited in these areas. In order to evaluate the effects of these no-take MPAs, the structure of their fish assemblages and of adjacent control areas without fishing restrictions were studied between 2011 (immediately after implementation) and 2013 (two years after implementation). A total of 4 sampling campaigns were conducted (summer 2011, winter 2012, summer 2013 and winter 2013) using trammel nets and bottom trawl. Ichthyofaunal assemblages from the no-take MPAs (treatment) were compared with adjacent areas (controls) and changes evaluated as a function of time since protection. Results revealed significant increase in fish abundance after the implementation of the no-take MPAs. Furthermore, significant differences in the structure of fish assemblages (abundance and fish size) between protected and neighbouring areas were rapidly observed upon the implementation of the no-take MPAs. In addition, specimens of larger size occurred more frequently within Ilha do Pessegueiro no-take MPA in the last year of the study. Overall, despite the young age of these no-take MPAs, changes on the structure of their fish assemblages were already evident after only two years of protection, indicating that management measures such as MPA designation may play an important role to promote fisheries sustainable exploitation as well as to protect species with conservation interest.